Body composition and torso muscle strength relationship in athletes - Akınoğlu, Bihter; Kocahan, Tuğba (Progress in Nutrition, 2019)
The purpose of this study is to investigate the relationship between body composition and torso isokinetic muscle strength among athletes and compare the parameters between both genders. The study was conducted on 76 female and 162 male athletes from various sports branches. Their body composition measurements were taken by the multifrequency bioelectric impedance analysis (Tanita MC-980, 1000 kH, Tokyo, Japan), whereas the torso flexor-extensor and the torso right-left rotator muscle strength by Isokinetic Dynamometer (D.& R. Ferstl GmbH, Hemau, Germany). The body fat percentage, fat mass, torso fat mass and torso fat percentage in female athletes were measured to be higher than the male ones, whereas their lean mass, muscle mass, torso muscle mass and whole torso isokinetic muscle strength values were lower (p>0.05). It was determined that there was a medium to high level of inverse relationship between fat percentage, fat mass, torso fat mass, torso fat percentage and torso muscle strength in all athletes (p<0.05). Moreover, there was a medium to high level of direct relationship between lean body mass, muscle mass, torso muscle mass and torso muscle strength (p<0.05). Female athletes had higher rate of body fat, and lower rate of muscle mass and torso muscle strength than male athletes, and the body composition parameters in all athletes were associated with the torso muscle strength. Therefore, we suggest that the athletes’ training should not only focus on increasing the body muscle strength, but also include special sessions for increasing the muscle mass and optimizing the body fat percentage of male and female athletes. Body composition of the athletes should be monitored regularly with a focus on these parameters.